CLINICAL PROFILE OF ADULT PATIENTS WITH HYPERGLYCEMIC CRISIS IN A PHILIPPINE TERTIARY MEDICAL CENTER, A TEN-YEAR RETROSPECTIVE STUDY - Agoncillo, Andre Luis; Pagsisihan, Daveric; Andag-Silva, Aimee (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The last study about diabetic ketoacidosis and hyperosmolar hyperglycemic state in our country was done 20 years ago. New diagnostic tools and therapeutic regimen may affect diabetes control, the researchers intend to know the changes in the clinical profile of patients with hyperglycemic crisis in the country. METHODOLOGY Descriptive study that utilized chart review. Included patients >18 years old, admitted in DLSUMC between 2007 and 2017 with a diagnosis of DKA or HHS based on ICOA-D-10 codes. Pregnancy excluded. Clinical characteristics, biochemical profile and precipitating factors were tallied. Descriptive statistics was used and Quantitative variables were reported as mean with standard deviation, while qualitative variables were reported as frequency and percentage. RESULTS 71 patients with DKA and HHS were included. Majority had DKA (53). 46 (64.79%) patients were known to have diabetes for 7-13 years. The mean Hba1c level is 9-17 mg/ dL that is higher than the developed countries. CBG range upon admission among DKA patients were 327 to 593 mg/dL and 427 to 693 mg/dL for HHS patients. Majority were discharged-improved. The most common presenting symptom was abdominal pain 19 (35.84%). The most common precipitating factor was infection, same in Thailand and US. CONCLUSION Hyperglycemic crises is common in Filipinos with T2DM which could suggest breaks in health services delivery and the unaffordability of insulin and new antidiabetic medications for patients with financial constraints as compared with developed countries like US and Japan. HbA1c levels did not significantly differ in other countries and this is consistent with the progressive nature of diabetes mellitus.